REVIEW OF ROAD DRAINAGE SYSTEM (CASE STUDY: JALAN CIGOMBONG KM 16 - KM 23) - Yahya Azura; Heny Purwanti; Wahyu Gendam Prakoso (Universitas Pakuan, 2019)
A good road drainage system is needed to ensure that road user activities are not disrupted due to rain puddles. The cause of inundation that occurs is land use change, there is no drainage channel, the channel is not well connected, the channel is closed due to widening of the road without considering drainage channels. Given this, research needs to be carried out on the condition of the existing drainage system as a material consideration for evaluating its feasibility and planning a drainage system that is able to overcome the inundation that occurs. Writing this final project refers to primary data and secondary data that already exist. The rainfall data came from the Climatology and Geophysics Meteorological Agency, Balai Besar Region II, Bogor Regency, which is the Darmaga huajn rainfall measurement station and the PUPR Binamarga Office of Bogor Regency. Meanwhile, to find out the dimensions of the existing drainage channels obtained by conducting surveys and direct observation to the field. Data analysis which was carried out was hydrological and hydraulics analysis. Hydrological analysis includes the analysis of rainfall frequency, determining the repeat period, calculating the concentration time, analyzing the rainfall intensity, and calculating the flow flow plan. Based on the results of hydrological analyzes, the hydraulics analysis is then performed, such as calculating the plan channel profile and calculating the height of the planned channel guard. From all of these analyzes, the results of the drainage study on the Cigombong KM 16 - KM 23 highway were carried out, that is, the entire capacity of the existing canals was not able to accommodate the planned flow discharge for a return period of 2 years 5 years 50 years. In addition, the results of the analyzes that have been carried out show that the rain that occurs during a certain period of time and a certain return period greatly affects the planned drainage channel profile and is due to the large amount of garbage in the channel which affects the reservoirs in the drainage that often occur frequently